Beowulf and the Celtic Tradition - Puhvel, Martin, 1933- (Book collections on Project MUSE., 2015)
Puhvel traces and evaluates the possible influences of Celtic tradition on the Anglo-Saxon epic poem Beowulf. He discusses theories of the origins of the poem, draws parallels between elements in Beowulf and in Celtic literary tradition, and suggests that the central plot of the poem, the conflict between Grendel and his mother, is "fundamentally indebted to Celtic folktale elements." The study is well documented and rich in references to Celtic literature, legend, and folklore.